Perbandingan Pengalaman-Preferensi Mahasiswa pada Pembelajaran Online vs Face to Face - Ismiati, Maria Bellaniar; Andayani, Sri (Jurnal Buana Informatika, 2021)
Abstract. Comparison of Student Experiences-Preferences in Online vs Face to Face Learning. Technology is increasingly developing, especially after the world has been hit by the COVID-19 virus pandemic. In the education sector, the learning process was carried out online, whereas before the pandemic it was carried out face to face. Of the two types of learning, there are often differences of opinion between students about which learning is better and more flexible. Based on this, this research is entitled Comparison of Students' Experience and Preferences on Online vs Face to Face Learning. This study uses a methodology, namely pre-field, field work, and data analysis. Data collection through interviews. Miles and Huberman's model is used for data reduction, data presentation, and conclusion drawing applied in data analysis. The results showed that student preferences for face to face learning were more than online learning, which was 75%, while the comparison of experiences felt by students was> 50% who chose face to face learning.Keywords: Online, Face to Face, Experience, PreferenceÂ Abstrak. Teknologi semakin berkembang, terutama setelah dunia dilanda oleh pandemi virus COVID-19. Di bidang pendidikan, proses pembelajaran dilakukan secara online sedangkan sebelum pandemi dilakukan secara face to face. Dari kedua jenis pembelajaran tersebut, sering terdapat beda pendapat antar mahasiswa mengenai mana pembelajaran yang lebih baik dan fleksibel. Berdasarkan hal tersebut, penelitian ini berjudul Perbandingan Pengalaman dan Preferensi Mahasiswa terhadap Pembelajaran Online vs Face to face. Penelitian ini menggunakan metodologi yaitu pra lapangan, pekerjaan lapangan, dan analisis data. Pengumpulan data melalui wawancara. Model Miles dan Huberman digunakan untuk reduksi data, penyajian data, dan penarikan kesimpulan diterapkan dalam analisis data. Hasil penelitian menjunjukkan preferensi mahasiswa terhadap pembelajaran face to face lebih banyak daripada pembelajaran online, yaitu sebanyak 75% sedangkan perbandingan pengalaman yang dirasakan oleh mahasiswa adalah sebanyak > 50% yang memilih pembelajaran secara face to face.Kata Kunci: Online, Face to Face, Pengalaman, Preferensi